Effectiveness of five biosolids as nitrogen sources to produce single and cumulative ryegrass harvests in two Australian soils - Corrêa, Rodrigo Studart (2016)
Biosolids have been produced by various stabilization processes of sewage sludge, but little attention has been given to the effects of such treatments on their effectiveness to supply nitrogen for plant growth. Here, we investigated these effects by cultivating Lolium perenne (ryegrass) in two Australian soils, a sandy Spodosol and a clayey Oxisol. Biosolids stabilized by either aerobic digestion, composting, CaO-liming, 250 oC heat-drying or solar irradiation of domestic sewage sludge were applied to soils at 10 increasing rates (0.25-8.0 dry Mg ha-1), and chemically fertilized soils were used as reference. Results showed that the stabilization processes affected biosolids-N agronomic rates and effectiveness to yield plant biomass, which was a function of organic-N contents mineralized in soils. In the short term, biosolids were from 1/5 (digested biosolids in Oxisol) to over twice (solar-irradiated biosolids in Spodosol) as effective as chemical fertilizer to produce a first single harvest. As long-term N-sources, they significantly increased the effectiveness to produce plant biomass, being from 2.0 to 4.1 times more effective than chemical fertilizer in Spodosol and 1.5-2.4 times in Oxisol. Biosolids could substitute for N fertilizer with similar or higher effectiveness to yield plant biomass, depending on the sewage sludge stabilization process, soil type and cultivation term considered. Therefore, the sound management of sewage products as N sources for crop production should consider the interaction among these factors rather than solely their N content.